Epidemio-clinical Profile of Atopic Dermatitis in Children in General Population in Parakou (Benin). - ADEGBIDI, HUGUES DANIEL GBADEBO; Agbessi, Nadège (My University, 2020)
Introduction: The aim of this study was to determine the epidemiological and clinical profile of atopic dermatitis (AD) in children in Parakou (Benin). Materials and Methods: This was a cross-sectional, descriptive, and analytical study of children aged 0–15 years old, selected after a two-stage cluster survey carried out. The diagnosis of AD was laid the basis of the criteria of the working group of the United Kingdom (UKWP). Data were analyzed with the Epi-info version 3.5.1. Results: A total of 157 children with AD were selected between 2160 (7.27%). Their mean age was 4.74 ± 4.33 years old. The sex ratio was 1.57 and the majority of children (80.25%) were doing their pushes regardless of the climatic season. The predominant elemental lesions were erythema (91.97%), crusts, erosions (74.45%), and vesicles (40.88%). Some children had at least two lesions. The most recognized minor signs of atopy were cutaneous xerosis (91.97%) and Dennie-Morgan sign (76.64%). Lesions were predominant in the retroauricular folds (41.61%). The dominant clinical forms were vulgar eczema (48.18%), lichenified forms (32.85%), and impetiginized forms (24.09%). According to the Scoring Atopic Dermatitis (SCORAD), 67.15% had moderate AD. Conclusion: The frequency of AD in children in Parakou is not negligible and the clinical manifestations are varied.
Keywords: Epidemiology; Clinical; Atopic dermatitis; Children; Parakou